KAJI ULANG PERBANDINGAN ANALISIS FONDASI TIANG PANCANG BERDASARKAN DATA SONDIR, DATA SPT DAN AKTUALISASI LAPANGAN (Studi Kasus Proyek Pembangunan Asrama BLKI Kota Tangerang Selatan) - Euis Amelia; Nur Hidayanti; Mohamad Mahrus (Journal of Sustainable Civil Engineering (JOSCE), 2019)
The foundation is one part of the structural building that plays an important role in building security. A strength and construction method secure foundation and appropriate building type is desirable in planning. The main function of the foundation is to pass the work load from the superstructure to the substructure. The selection of appropriate foundations and in accordance with the type of building and soil conditions must be carefully calculated. Along with the development and advancement of technology, pile foundation and bored pile is widely used for the construction of high-rise buildings, flyovers, bridges and other constructions with different functions. Therefore the determination of the type of foundation is very important in terms of distribution of styles to be channeled, settlement, method of implementation and financing.